On the angular dependence of the vicinal fluorine-fluorine coupling constant in 1,2-difluoroethane: deviation from a karplus-like shape - Provasi, Patricio Federico (2006)
The angular dependence of the vicinal fluorine−fluorine coupling constant, 3JFF, for 1,2-difluoroethane has been investigated with several polarization propagator methods. 3JFF and its four Ramsey contributions were calculated using the random phase approximation (RPA), its multiconfigurational generalization, and both second-order polarization propagator approximations (SOPPA and SOPPA(CCSD)), using locally dense basis sets. The geometries were optimized for each dihedral angle at the level of density functional theory using the B3LYP functional and fourth-order Møller−Plesset perturbation theory. The resulting coupling constant curves were fitted to a cosine series with 8 coefficients. Our results are compared with those obtained previously and values estimated from experiment. It is found that the inclusion of electron correlation in the calculation of 3JFF reduces the absolute values. This is mainly due to changes in the FC contribution, which for dihedral angles around the trans conformation even changes its sign. This sign change is responsible for the breakdown of the Karplus-like curve.